Photoionized argon plasmas induced with intense soft x-ray and extreme ultraviolet pulses. (20th October 2015) - Bartnik, A; Wachulak, P; Fok, T; Węgrzyński, Ł; Fiedorowicz, H; Skrzeczanowski, W; Pisarczyk, T; Chodukowski, T; Kalinowska, Z; Dudzak, R; Dostal, J; Krousky, E; et al.
Abstract: In this work, photoionized plasmas were created by irradiation of gaseous argon with soft x-ray (SXR) and extreme ultraviolet (EUV) intense radiation pulses. Two different laser-produced plasma sources, employing a low energy Nd:YAG laser and a high energy iodine laser system (PALS), were used for creation of photoionized plasmas. In both cases the EUV or SXR beam irradiated the Ar stream, injected into a vacuum chamber synchronously with the radiation pulse. Emission spectra, measured for the Ar photoionized plasmas indicated strong differences in ionization degree for plasmas produced using low and high energy systems. In case of the the EUV driving pulses, emission lines corresponding to neutral atoms and singly charged ions were observed. In case of the SXR pulses utilized for the photoionized plasma creation, only Ar V–VIII emission lines were recorded. Additionally, electron density measurements were performed by laser interferometry employing a femtosecond laser system synchronized with the irradiating system. Maximum electron density for the Ar photoionized plasma, induced using the high energy system, reached 1.9 · 10 18 cm −3 . Interferometric measurements performed for the moment of maximum intensity of the main laser pulse ( t = 0) revealed no fringe shift. Detection limit for the interferometric measurements was estimated. It allowed to estimate the upper limit for electron density at t = 0 as 5 · 10 16 cm −3 .